Creative Idea & Unique Design : Objet2 - Archiworld Co. , Ltd.; Archiworld Co. , Ltd. (Korea : Archiworld Co. , Ltd., 2000)
From Travel + Leisure, the world's leading travel magazine, comes the newest edition of 100 Greatest Trips, an invaluable compendium of the year's most distinctive destinations. Whether your dream is to escape to a thatched-roof safari camp in the heart of a South African game reserve, explore the cobblestoned streets of Paris's hidden neighborhoods, or find the best spot to enjoy a glass of Prosecco along the Tyrrhenian Sea in Capri, Italy, 100 Greatest Trips points the way to the places you'll want to go next with expert reporting on style, culture, food, and design, and stunning photography that captivates and inspires.
Includes index.
Keywords: Scenery -- Design; Chair -- Design; Guidebooks